2009
DOI: 10.1017/s0022215109990958
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided, endoscopic removal of migrated titanium dental implants from maxillary sinus: two cases

Abstract: Both patients underwent successful removal of their migrated dental implants with no complications, and neither required any follow-up intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 6 publications
1
22
0
6
Order By: Relevance
“…8 Complications of dental implants involving the sinonasal cavities are less common and include sinusitis and implant migration into the paranasal sinuses, which are found in the literature only in case reports and small case series. [9][10][11] In the present case report, the CT images obtained during workup of the SNT infection showed that the implant was in an appropriate position within the alveolar ridge and did not appear to have migrated superiorly toward the sinonasal cavity. Despite being within a few millimeters of the infected tooth, the implant did not become infected and was retained without issue during and after treatment of the SNT.…”
Section: Discussionsupporting
confidence: 49%
“…8 Complications of dental implants involving the sinonasal cavities are less common and include sinusitis and implant migration into the paranasal sinuses, which are found in the literature only in case reports and small case series. [9][10][11] In the present case report, the CT images obtained during workup of the SNT infection showed that the implant was in an appropriate position within the alveolar ridge and did not appear to have migrated superiorly toward the sinonasal cavity. Despite being within a few millimeters of the infected tooth, the implant did not become infected and was retained without issue during and after treatment of the SNT.…”
Section: Discussionsupporting
confidence: 49%
“…Another possibility is to remove the implant by transnasal approach, usually through middle meatal antrostomy (Ramotar et al, 2010;Lubbe 2008). Such approach is particularly indicated if concomitant sinusitis is present, since it provides both an opportunity to remove displaced implant and to improve ventilation and drainage of affected sinus (Kim et al, 2007).…”
Section: Endoscopic Surgery For Treatment Of Implant-related Complicamentioning
confidence: 99%
“…When this happens, the implant remains, in almost all the cases, lodged inside the sinus (Chappuis et al, 2009;Borgonovo et al, 2010), and can be removed a few days later by opening the lateral wall of the maxillary sinus (Haben et al, 2003) (Fig. 5), or by endoscopic via through a nasal window; a process that allows a considerable good access to the zone and a lower postoperative morbidity than when it is performed intraorally (Haben et al, 2003;Felisati et al, 2007;Galindo et al, 2005;Ramotar et al, 2010). In these intra-or postoperative cases, authors recommend the immediate removal of the implant lodged in the maxillary sinus (Ramotar et al, 2010;Galindo et al, 2005;Felisati et al, 2007;Haben et al, 2003) through an intraoral or trans-nasal via that will prevent further associated complications; although it is in general asymptomatic condition, most patients suffer from a marked sinusitis.…”
Section: Implant Displacementmentioning
confidence: 99%
“…5), or by endoscopic via through a nasal window; a process that allows a considerable good access to the zone and a lower postoperative morbidity than when it is performed intraorally (Haben et al, 2003;Felisati et al, 2007;Galindo et al, 2005;Ramotar et al, 2010). In these intra-or postoperative cases, authors recommend the immediate removal of the implant lodged in the maxillary sinus (Ramotar et al, 2010;Galindo et al, 2005;Felisati et al, 2007;Haben et al, 2003) through an intraoral or trans-nasal via that will prevent further associated complications; although it is in general asymptomatic condition, most patients suffer from a marked sinusitis. Another complication, in addition to the acute or chronic sinusitis, is the implant intrusion that occurs when it is not removed during its migration Felisati et al and Haben et al (Felisati et al, 2007;Haben et al, 2003) reported two cases of intrusions in which they found that two fixations had displaced from the maxillary sinus into the sphenoidal and ethmoidal sinuses, respectively, when they tried to remove them; the solution, though, should be to use an endoscopic nasal via.…”
Section: Implant Displacementmentioning
confidence: 99%